LIFTING OF MULTIPHASE DEGENERACY BY QUANTUM FLUCTUATIONS - Harris, A; Micheletti, C; Yeomans, J (1995)
We study the effect of quantum fluctuations on the multiphase point of the Heisenberg model with first- and second-neighbor competing interactions and strong uniaxial spin anisotropy D. By studying the structure of perturbation theory we show that the multiphase degeneracy which exists for S= (i.e., for the axial next-nearest-neighbor Ising model) is lifted and that the effect of quantum fluctuations is to stabilize a sequence of phases of wavelength 4,6,8,.... This sequence is probably an infinite one. We also show that quantum fluctuations can mediate an infinite sequence of layering transitions through which an interface can unbind from a wall. © 1995 The American Physical Society.